Measuring Financial Performance of PT. Pos Indonesia During The E-Commerce Booming - Sasotya Pratama (International Journal of Business Studies, 2018)
Advancement of telecommunications technology and Internet protocol has encouraged the development of services through electronic commerce (e-commerce). The growth ofover 35% per year has been achieved by the industry since 2013 in Indonesia. More than ten companies operate in the industry. In line with the development of e-commerce services, also developed supporting industries such as logistics, to deliver products purchased over the Internet. There are about three big private companies in the courier industries, and the only state-owned enterprises (SOEs) in the courier industry is PT. Pos Indonesia (PTPI). The purpose of this study is to measure and evaluate the inancial health condition of PTPI for periods of 2009- 2015 by investigating its inancial ratios included return on equity,return on investment, cash ratio, current ratio, collection period,inventory turnover, total asset turnover, and total equity to the total asset. The result shows achieved inancial health condition of PTPI and can be used to advise further improvements